Table of Content - - (Arab Journal for Sciences and Research Publishing, 2025)
Table of Content: 1. The Role of Modern Information Technologies in Promoting Scientific Research in Saudi Universities: Challenges, Requirements, and Future Opportunities Ms. Ashwaq Abdulhakeem Alsabaan 2. The Impact of Virtual Reality Technologies in Digital Media on Audience Experience: An Applied Study on Real Estate Events in The Kingdom of Saudi Arabia During the Year 2025 Dr. Sara Saad Al-Dawsari,Dr. Sadiq Ali Mubarak Al-Shuwaikhat 3. The Implications of Polygamy on the Demographic Reality in Palestinian Society and the Stance of Israeli Civil Laws Towards It Dr. Samy Garad Abu Freach 4. The Philosophy of Divinity: From Platonism to Orthodoxy – A Study in the Thought of Theodoret of Cyrrhus Dr. Rony Emil Saiid 5. Translation is a cultural and human civilizational manifestation, and technical skills for the rapprochement of peoples and nations Dr. Jehad Faiz Al-Islam 6. MATLAB Implementation of Effects of Fifth Generation on Free Space Eng. Rayan Abdelazeem Haboub, Prof. Khalid Hamid Bilal